A cost effective method for immobilization of Cu and Ni polluted river sediment with nZVI synthesized from leaf extract. (January 2021) - Slijepčević, Nataša; Pilipović, Dragana Tomašević; Kerkez, Đurđa; Krčmar, Dejan; Bečelić-Tomin, Milena; Beljin, Jelena; Dalmacija, Božo
Abstract: This study investigates the performance of oak (OL) and mulberry (ML) leaves for synthesized of nanoscale zero-valent iron (nZVI), in immobilizing Cu and Ni in contaminated sediment. Characterization of synthesized Fe nanoparticles from oak and mulberry leaf extracts demonstrated that they are nontoxic and stabile nanomaterials for application in the sediment remediation. Effectiveness of stabilization process was performed by microwave-assisted sequential extraction procedure (MWSE) and single-step leaching tests which have been applied to evaluate the metal extraction potential. This research showed that OL-nZVI and ML-nZVI were effective in transforming available Cu and Ni to stable fraction. The maximum residual percentage of Cu increased by 76% and 73%, and for Ni 81% and 80%, respectively, with addition of 5% OL-nZVI and 5% ML-nZVI. Used single-step leaching tests (Toxicity Characteristic Leaching Procedure–TCLP and German standard test- DIN) indicated that all stabilized samples can be considered as non-hazardous waste, as all leached metal concentrations met the appropriate set criteria. Cost analysis showed that the operating cost for contaminated sediment treatment with green synthesized nZVI are 50.37 €/m3/per year. This work provides a new insight into the immobilization mechanism and environmental impact of Cu and Ni in contaminated sediment and potential way of treatment with OL-nZVI and ML-nZVI. Generally, nZVI can be an effective and versatile tool for stabilization of sediment polluted with toxic metals. Graphical abstract: Image 1 Highlights: A cost effective and environmental friendly way is adopted to prepare nano zero valent iron (nZVI). Oak (OL) and mulberry (ML) leaf extract behave as efficient reducing and capping agents. ML-nZVI and OL-nZVI were effective in transforming labile metals to stable fraction. Results show that after stabilization all samples were non-hazardous. ML-nZVI and OL-nZVI proved to be effective immobilization agents.